O Regionalismo nos Estados Unitário, Federal e Regional - Pessoa, Emanuel de Abreu (2008)
Initially, are verified the three elements that each and every corporation that intends to be a State must have, namely, people, territory and government. The concepts alike are inquired, such as Nation, population and patria; the different theories about State territory; and the power of government, demonstrating that sovereignty is not a constituent element of the State, but only a quality of that power. The States organize themselves in a particular manner, accordingly to specific circumstances. Nevertheless, it is possible to group them, in compliance with presenting similar attributes, under the unitary, federal or regional form. It is examined the unitary State first, which represents the most centralized form, being averred it bears strictly administrative decentralization, trough autarchies. Once being the most common form of State, adopted by the majority of the modern national States, besides it the unions of States are studied. In the sequence, it is testified the rise of the Federation. The main thesis on federalism and the peculiarities of a Federation are also taken in account, specially the laws of autonomy and participation and the existence of a Constitutional Court. The regional State is inspected through the analysis of the political organization of Spain and Italy, noticed the characteristics of the Autonomous Communities and of the Regions, making a brief commentary on the Portuguese regionalism. It is explored the cooperative federalism to, directly afterwards, deal with the Brazilian regionalism, showing how the former consolidated the latter. Finally, it is exposed the regional federalism, potential solution for Brazil’s regional inequalities.